Emotional State of the Pre-Service Teachers Prior to Field Study: Basis for Support and Monitoring Program - Bautista, Mechel; Jamie Nhilen Apostol; Raymond Malibiran; Kristoffer Paul Obispo; John Mark Asio (Formosa Journal of Multidisciplinary Research, 2024)
The proponents aim to assess the emotional state of the pre-service teachers from a tertiary education institution in Olongapo City, Philippines. A total of 185 pre-service teachers participated in the study using a descriptive research design. To gather enough information about the emotional state of the respondents, the study used a standardized instrument, the DASS-21, to assess three aspects of emotional status: depression, anxiety, and stress levels of the respondents. Afterward, the proponents then calculated the descriptive statistics like frequency and percentage. Results show that the pre-service teachers have normal to moderate levels of depression, a moderate to extreme degree of anxiety, and a normal to moderate level of stress in most of them.